Neurobiological Evidence for the Primacy of Mania Hypothesis - D. Kotzalidis, Georgios; Rapinesi, Chiara; Savoja, Valeria; Cuomo, Ilaria; Simonetti, Alessio; Ambrosi, Elisa; Panaccione, Isabella; Gubbini, Silvia; De Rossi, Pietro; De Chiara, Lavinia; Janiri, Delfina; Sani, Gabriele; et al. (Current Neuropharmacology, 2017)
Background: Athanasios Koukopoulos proposed the primacy of mania hypothesis (PoM) in a 2006 book chapter and later, in two peer-reviewed papers with Nassir Ghaemi and other collaborators. This hypothesis supports that in bipolar disorder, mania leads to depression, while depression does not lead to mania. Objective: To identify evidence in literature that supports or falsifies this hypothesis. Method: We searched the medical literature (PubMed, Embase, PsycINFO, and the Cochrane Library) for peer-reviewed papers on the primacy of mania, the default mode function of the brain in normal people and in bipolar disorder patients, and on illusion superiority until 6 June, 2016. Papers resulting from searches were considered for appropriateness to our objective. We adopted the PRISMA method for our review. The search for consistency with PoM was filtered through the neurobiological results of superiority illusion studies. Results: Out of a grand total of 139 records, 59 were included in our analysis. Of these, 36 were of uncertain value as to the primacy of mania hypothesis, 22 favoured it, and 1 was contrary, but the latter pooled patients in their manic and depressive phases, so to invalidate possible conclusions about its consistency with regard to PoM. All considered studies were not focused on PoM or superiority illusion, hence most of their results were, as expected, unrelated to the circuitry involved in superiority illusion. A considerable amount of evidence is consistent with the hypothesis, although indirectly so. Limitations. Only few studies compared manic with depressive phases, with the majority including patients in euthymia. Conclusion: It is possible that humans have a natural tendency for elation/optimism and positive selfconsideration, that are more akin to mania; the depressive state could be a consequence of frustrated or unsustainable mania. This would be consistent with PoM.
Keywords: Primacy of Mania Hypothesis